Identification And Potential Of Traditional Foods In Lekuk 50 Tumbi Lempur Tourism Village As A Culinary Tourism Attraction - Araruna, Agre; Kasmita, Kasmita (Universitas Negeri Padang, 2024)
The purposeof this study was to describe the traditional food varities in Lekuk 50 Tumbi Tourism Village in terms of culinary tourism indicators, namely uniqueness, originality, authenticity and diversity. The research method in this thesis uses descriptive research methods with qualitative data. The goals and research statements guided the analysis and interpretation of the collected data. Using a non-probability sample technique called snowball sampling, informants were identified. Through observation, documentation, and interviewing, data was gathered.The results of the study show that traditional food in the village has strong characteristics and is able to create an unforgettable culinary experience for tourists. Overall, the traditional food at Lekuk 50 Tumbi Lempur Tourism Village has great potential as a main attraction in culinary tourism. The combination of uniqueness, authenticity, originality and diversity creates an immersive and unforgettable culinary experience for tourists. With the right development strategy, the village can maximize this potential, strengthen the local economy, and introduce its rich cultural heritage to the world. Through collaborative and sustainable efforts, Lekuk 50 Tumbi Lempur Tourism Village has the potential to become a culinary destination that not only spoils the tongue, but also touches the soul with authentic cultural diversity.Keyword: